2021
DOI: 10.1111/ajag.12980
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the increased risk of dementia found in the Torres Strait

Abstract: Objective: To identify the specific risk factors for dementia in the Torres Strait.Methods: This research was conducted as part of a cross-sectional dementia prevalence study conducted in the Torres Strait. Participants underwent a comprehensive health assessment, where data on risk factors were collected, and a Geriatrician assessment, which was used to establish dementia diagnoses. Results: A total of 276 Torres Strait residents aged between 45 and 93 participated in the study. Cerebrovascular disease, chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Albuminuria is proposed to be a sensitive biomarker of systemic microcirculatory dysfunction, including damage to the microvasculature of the brain ( 23 ). Although our results require support with more data, they concur with an association between chronic kidney disease and dementia among residents of the Torres Strait and Northern Peninsula Area identified elsewhere ( 17 ). In terms of international applicability, in populations where both dementia and kidney disease are prevalent, the impact of kidney health in earlier life may be important.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Albuminuria is proposed to be a sensitive biomarker of systemic microcirculatory dysfunction, including damage to the microvasculature of the brain ( 23 ). Although our results require support with more data, they concur with an association between chronic kidney disease and dementia among residents of the Torres Strait and Northern Peninsula Area identified elsewhere ( 17 ). In terms of international applicability, in populations where both dementia and kidney disease are prevalent, the impact of kidney health in earlier life may be important.…”
Section: Discussionsupporting
confidence: 89%
“…A recent cross-sectional study of 276 Torres Strait Islander and Aboriginal peoples from this region indicated this population had a threefold risk of dementia compared with other Australians (the Dementia Prevalence Study, 2015–2018) ( 11 ). The same project reported that cerebrovascular disease and chronic kidney disease were associated with dementia risk ( 17 ). Participants in this study were also diagnosed with cognitive impairment not dementia (CIND) (i.e., mild cognitive impairment) if they had cognitive decline beyond age expectations and were functionally intact.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Among older Indigenous residents of the Torres Strait, vascular risk factors such as diabetes have been identified as potential drivers of the elevated dementia rates. 14 The results of the current study may provide some evidence of the detrimental effect of a vascular risk early in this process. However, this proposition remains far from conclusive given the small effect size in our study and the broader uncertainty about the continuum between diabetes‐associated cognitive decrements and later dementia.…”
Section: Discussionmentioning
confidence: 65%
“…Recent evidence suggests that vascular risk factors, including diabetes, may be associated with higher rates of dementia among Indigenous Australians living in the Torres Strait. 13 , 14 Understanding more about the cognitive implications of diabetes in these vulnerable populations could therefore improve understanding of the development of diabetes‐related brain disease and assist with targeting preventative health activities.…”
Section: Introductionmentioning
confidence: 99%
“…In this population of approximately 9,000 people, the rate of dementia in those aged 45 years and over was almost three times higher than overall Australian estimates for the same age group. 17 Stroke and chronic kidney disease were associated with an individual's risk of having dementia, 18 while rates of other vascular diseases, such as diabetes, are also historically high in this population. 19 , 20 , 21 , 22 , 23 , 24 There are currently no published estimates of how much these diseases and their associated risk factors contribute to the burden of dementia for this population or how they will shape the future burden.…”
Section: Introductionmentioning
confidence: 95%